Z Kościuszki na Pomorską - Pietrych, Krystyna (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2025)
The text covers the move of the Department of Philology of the University of Łodź from its previous seat at 65 Kościuszki Av. to the new modern building at 171/173 Pomorska St. Photographs depict the building of the former seat of the German Reform School erected by the German School Association in Łódź in 1909–10. The building housed the School until WW2, during the Nazi occupation a German school was located there, and after the war – various secondary schools. In 1970-2014, the building housed the Department of Philology of the University of Łódź. In 1981, it was the headquarters of the nationwide student strike, which ended after an agreement was signed with the Minister of Science, Higher Education and Technology of the Communist Poland. Thanks to the agreement the Independent Student Association was officially registered and Polish universities gained autonomy.